2016
DOI: 10.1093/jamia/ocv160
|View full text |Cite
|
Sign up to set email alerts
|

Interactive tools for inpatient medication tracking: a multi-phase study with cardiothoracic surgery patients

Abstract: Inpatient medication-tracking tools, when designed to meet patients' needs, can play an important role in fostering patient participation in their own care and patient-provider communication during a hospital stay.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
66
0
5

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 38 publications
(73 citation statements)
references
References 43 publications
0
66
0
5
Order By: Relevance
“…Valdez et al recognize tracking as an important part of patient work [52], and researchers have begun to explore the potential of tracking support tools in this space (e.g. [57] and others reviewed in the discussion section). However, tracking remains a difficult task for patients in the hospital.…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…Valdez et al recognize tracking as an important part of patient work [52], and researchers have begun to explore the potential of tracking support tools in this space (e.g. [57] and others reviewed in the discussion section). However, tracking remains a difficult task for patients in the hospital.…”
Section: Related Workmentioning
confidence: 99%
“…Although researchers have begun to explore better ways to present data provided to patients by health care organizations [22,60], much work remains to be done on how to support patient-provider collaboration in the hospital, where clinicians collect and control the bulk of patient data. Thus far, studies in this space have shown that hospitalized patients value the ability to ask their clinicians questions electronically [57], “triage” their inquiries [57], and set personalized health goals [10]. Studies of technology-mediated patient-clinician collaboration in the hospital [12] and after discharge [5] have shown improved outcomes as a result of this collaboration, underscoring the importance of properly supporting this collaboration.…”
Section: Related Workmentioning
confidence: 99%
“…To assist patients in understanding changes to medication therapies during their stay, we developed information processing techniques to create summaries of medication schedules, updated dynamically as medications were ordered, administered, and discontinued [1,5,7]. These summaries included interactive graphical elements in the user interface to display medication information, including medication name, dose, timing, indication, and a descriptive educational summary.…”
Section: Delivering Near Real Time Patient-accessible Information Dumentioning
confidence: 99%
“…Postoperative cardiothoracic surgery patients used the technology in a pilot study, demonstrating a high level of engagement with the tools. These patients' assessment of health status and care progress improved with the ability to track medication changes, and improved communication regarding their home medication list [7].…”
Section: Delivering Near Real Time Patient-accessible Information Dumentioning
confidence: 99%
“…While studies that have explored the effect of IPPs in specific contexts go back to 2011 [13][14][15], adoption of large scale commercial IPPs has generally been slow. One of the first such implementations occurred in 2013 at The Ohio State University Wexner Medical Center (OSU) with Epic Systems' MyChart Bedside (MCB) product.…”
Section: Introductionmentioning
confidence: 99%